Impact of Engine Downsizing on Fuel Economy and Carbon Footprint : A Simplified Modeling Approach - Priyono Priyono; Damianus Manesi; Edy Suprapto; Fahrizal Fahrizal; Wofrid E. Bianome (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Global climate change demands immediate technological advancements, particularly in the transport industry that continues to use fossil fuels. One viable solution is to reduce the size of vehicle engines to make them more fuel-efficient and lower carbon emissions. The purpose of this research is to assess the effect of reducing engine size on fuel consumption and CO₂ emissions in low-cost green car hatchbacks in Indonesia. The technique employed is straightforward analytical modeling, employing Pearson correlation analysis and linear regression among three significant variables: engine capacity, fuel economy, and CO₂ emission. The data are obtained from the technical specifications of four hatchback automobile models, all of which have an engine capacity of less than 1,200 cc. Findings indicate that smaller engine capacity is accompanied by greater fuel economy and lower carbon emissions. The lowest engine size of 998 cc is used in the Toyota Agya, which demonstrates the most efficient fuel and lowest emissions. The statistical analysis shows that there is an inverse relationship between engine size and fuel efficiency, but a positive relationship between engine size and CO₂ emissions. The limitation of sample size causes reduced statistical power of the model. In conclusion, engine downsizing can prove to be a productive approach in promoting green schemes, but additional research with a larger data set and other determinants must be undertaken to establish a more advanced and precise model.